ORALXAN SAPAROVA ShÍǴARMALARÍNÍŃ JANRLÍQ HÁM KOMPOZICIYALÍQ ÓZGEShELIKLERI - Kamalova, D. (SCIENCE and SOCIETY, 2025)
The article analyzes the writer Oralkhan Saparova, who appears in the Karakalpak literary process with his works of art, using the example of his works included in the books “Ómir sabaqları”, “Qaydasań Chinara?!..”, “Táǵdir soqpaqları” and “Ármanlar sınǵan kún”. This reveals the writer’s choice of topic and unique style.